Early gastric cancer with splenic artery aneurysm successfully treated with laparoscopic distal gastrectomy after endovascular coil embolization: A case report. Issue 3 (14th December 2020) - Saito, Kazuyuki; Yamagata, Yukinori; Hakozaki, Yuhei; Nakata, Manabu; Oya, Masatoshi
Abstract: Splenic artery aneurysm (SAA) is a relatively rare disease. Most patients with SAA have no symptoms, and detection is incidental detection. The incidence of rupture is not particularly high, but the mortality rate of ruptured SAAs is high. The main treatment for gastric cancer is gastrectomy with lymph node dissection, with dissection around the celiac artery suggested to be the most important. A 68‐year‐old woman with early gastric cancer in the lesser curvature of the lower gastric corpus was referred to our hospital. CT showed no remarkable findings except for a saccular SAA (diameter, 1.5 cm). We planned laparoscopic distal gastrectomy. However, because the SAA was close to the surgical field and its saccular shape created a rupture risk, we performed interventional radiology for SAA before surgery. One month later, laparoscopic distal gastrectomy with D1+ was performed successfully. The patient has remained disease‐free in the 51 months since the operation.